Evolución humana y el ADN mítocondríal - Amat Olazaval, Hernan (2007)
Whit this essay, we want 10show a histon SUml1U1f:"of our predecessors sil/ce we tout of the chimpanzee lineage 5 or 6 millions 0(1ears ago until the appearance of the Horno sapicns sapíens, as a result of man.l' significant evolutionary changes. Also we present the most importunt researches of the last three decades about the human evolution, the genetic ofpopulation and theDNA mt.,proving that everybody camefrom Al/ka. 111 this time ofsignificant paieontologv and archaeology discoveries that generare permunent discussions around the human evolution, each discovery compels us tu draw new branches of the genealogical free of the human being. The reader can follow the predetermimined itinerary (O understand such apolemic topic. meet one general theory or remake a specific history. taking part in the critics to the resents theories.